Big Data and Dementia: Charting the Route Ahead for Research, Ethics, and Policy - Ienca, Marcello; Vayena, Effy; Blasimme, Alessandro (Frontiers in Medicine, 2018)
Emerging trends in pervasive computing and medical informatics are creating the possibility for large-scale collection, sharing, aggregation and analysis of unprecedented volumes of data, a phenomenon commonly known as big data. In this contribution, we review the existing scientific literature on big data approaches to dementia, as well as commercially available mobile-based applications in this domain. Based on these analyses, we identify the major promises and challenges associated with big data trends in dementia research and care. Our analysis suggests that big data approaches to dementia research and care hold promise to improve current preventive and predictive models, to shed light on the aetiology of the disease, to enable earlier diagnosis, to optimize resource allocation and to deliver more tailored treatments to patients with specific disease trajectories. Such promissory outlook, however, has not materialized yet, and raises a number of technical, scientific, ethical and regulatory challenges. This paper provides an assessment of these challenges and charts the route ahead for research, ethics and policy.